2021
DOI: 10.1051/shsconf/20219201009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 global pandemic on tourists’ preferences and marketing mix of accommodation facilities – case study from Czech Republic

Abstract: Research background: Two related effects of the COVID-19 global pandemic on tourism and hospitality in the Czech Republic are already evident for the upcoming summer months. In the first place, it is the effect on the Czech tourists’ preferences. The pandemic forced them to reconsider their plans and, as a result, it is evident that more tourists will spend summer only in the Czech Republic. This change in preferences is connected with a second effect, concerning the strategies of the domestic accommodation fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…They also confirmed that customers started to take safety measurements into account, while the influence of all the considered demographic factors was proclaimed negative (Kock, 2020). The study on Czech and Slovak customers supports these findings and adds, that these customers markedly started to prefer domestic travelling connected to sightseeing and staying in nature (Dusek & Sagapova, 2021).…”
Section: Preference Changes For Transportation Purchases Caused By Th...supporting
confidence: 65%
“…They also confirmed that customers started to take safety measurements into account, while the influence of all the considered demographic factors was proclaimed negative (Kock, 2020). The study on Czech and Slovak customers supports these findings and adds, that these customers markedly started to prefer domestic travelling connected to sightseeing and staying in nature (Dusek & Sagapova, 2021).…”
Section: Preference Changes For Transportation Purchases Caused By Th...supporting
confidence: 65%
“…Local tourists’ accommodation preferences may be different from those of foreign tourists, and domestic tourists usually will not choose expensive destinations overcrowded by foreigners and tourists-oriented destinations. Instead, they will seek out surrounding, cheaper destinations during the pandemic ( Dušek & Sagapova, 2021 ), leading to the suburbanization of the reservation distribution. According to the corresponding changes, we should also further consider whether this kind of suburbanization will continue for a long time to formulate more effective policy adjustments and responses.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous tourists look forward to experiencing nature, the sea, mountains, and outdoor activities in the open air. Visitors prefer to plan their vacations, including restaurants and transportation services in their chosen tourist destinations (Dušek & Sagapova, 2021;Yuni, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…If there is a systemized mitigation at the tourist spot, a standard operating procedure, or a system that limits the number of visitors to tourist attractions, is the visitor's health and safety guaranteed, etc., then the visitors will validate that. People tend to travel within their own countries (Dušek & Sagapova, 2021). On vacation, people are more likely to stay in their own country, and large families with young children are more likely to travel short distances than other travelers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation